Printed Neuromorphic Devices Based on Printed Carbon Nanotube Thin‐Film Transistors - Feng, Ping; Xu, Weiwei; Yang, Yi; Wan, Xiang; Shi, Yi; Wan, Qing; Zhao, Jianwen; Cui, Zheng (Advanced functional materials, 2017)
Hardware implementation of artificial synapse/neuron by electronic/ionic hybrid devices is of great interest for brain‐inspired neuromorphic systems. At the same time, printed electronics have received considerable interest in recent years. Here, printed dual‐gate carbon‐nanotube thin‐film transistors with very high saturation field‐effect mobility (≈269 cm2 V−1 s–1) are proposed for artificial synapse application. Some important synaptic behaviors including paired‐pulse facilitation (PPF), and signal filtering characteristics are successfully emulated in such printed artificial synapses. The PPF index can be modulated by spike width and spike interval of presynaptic impulse voltages. The results present a printable approach to fabricate artificial synaptic devices for neuromorphic systems. Printed dual‐gate carbon‐nanotube thin‐film transistors with very high saturation field‐effect mobility are proposed for artificial synapse application. Important synaptic behaviors including paired‐pulse facilitation and signal filtering characteristics are successfully emulated. The PPF index can be modulated by spike interval and spike width of presynaptic voltages. This work presents a printable approach to fabricate synaptic devices for neuromorphic system applications.